Interleukin 6 polymorphism corresponds to the number of severely stenosed coronary arteries. - Myśliwska, J; Wieckiewicz, J; Hak, L; Siebert, J; Rogowski, J; Szyndler, K; Myśliwski, A (2006)
IL6 gene promoter polymorphisms may influence the outcome of cardiovascular diseases. The aim of our study was to find out whether the -174G>C polymorphism, as well as the IL6 secretory profile, may be linked to the number of severely (> or = 75%) occluded coronary arteries in patients with advanced coronary heart disease (CHD). Three hundred and twenty patients awaiting elective coronary artery bypass grafting were enrolled into the study. Blood was taken the day before surgery. The PCR-RFLP method was used for IL6 gene polymorphism analysis. Spontaneous IL6 release was measured by bioassay in supernatants of whole blood cell cultures (WBCC) incubated for 24 h and 48 h. We found that significantly more patients with triple vessel disease were found within the -174GG group as compared to the -174GC and CC genotype carriers. The highest IL6 serum levels were found in the -174GG and the lowest in the -174CC genotype patients. Spontaneous in vitro IL6 secretion appeared to be significantly higher at all time points in the -174GG as compared to the CC and GC genotype carriers. The serum concentration of IL6 and the spontaneous IL6 secretion were directly related to the number of obstructed coronary vessels. Our results emphasize the role of IL6 as an important, non-classical risk factor predicting the number of severely affected coronary vessels.